Fostering technological progress in space exploration to drive Sustainable Development Goals - Caro-Carretero, Raquel (European Public & Social Innovation Review, 2025)
Introduction: Exploration of space and gathering data on its atmospheric conditions could drive the development of advanced space technologies, such as atmospheric sensors and remote monitoring systems. Then, scientific research in seemingly distant areas, such as astrophysics and space exploration, can contribute to the achievement of the SDGs by promoting innovation and sustainable technological development. Methodology: We present an automated four-step detection algorithm for identification of photoelectron peaks based on a short-term-average/long-term-average phase picker taken along a characteristic function. Additional analysis is applied to the longer signal window after the declared detection to characterize photoelectron peaks and discard noise disturbances. Results: The modular design of the algorithm enables the substitution of alternative strategies in any of the four steps and the rapid implementation on new datasets. Discussion: The utility of the algorithm is illustrated through an overview example based on data from all available Titan flybys. The knowledge about photoelectron peaks in Titan's atmosphere could offer insights that could be valuable for addressing climate change on Earth. Conclusions: Understanding planetary plasma environments, including their interaction with the solar wind and other space weather phenomena, can indirectly contribute to our understanding of Earth's climate system.